Talking with People about to Die. Issue 5922 (6th July 1974) - Hinton, J.
Abstract : Sixty patients receiving care for terminal cancer commented on their discussions with doctors and nurses. Of these, 40 had some awareness of dying and none disapproved of open discussion. Of the 21 reporting little or no truthful conversations with staff, nine were critical, but the other 12 were not dissatisfied, including some aware of the prognosis.